2020
DOI: 10.1177/1357633x20901400
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and acceptance of a home-based telemonitoring application used by multi-morbid patients aged 65 years and older

Abstract: Introduction Currently, there are only a small number of comprehensive study results on adherence and acceptance of telemonitoring applications (TMAs) regarding multi-morbid older patients. The ATMoSPHAERE study aimed to develop an information and communication platform for an intersectoral networking of, for example, general practitioners, therapists, social services and the multi-morbid older patient. Methods The study presented was designed as a longitudinal bicentric intervention study which focused on mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 60 publications
3
23
0
2
Order By: Relevance
“…La estrategia que combina telemedicina y seguimiento proactivo ha sido bien aceptada por los pacientes (solo 2 no dieron su consentimiento y hubo un alta voluntaria). Al contrario de lo que sucede en otras enfermedades, el seguimiento se completó sin grandes problemas en la mayoría de los enfermos [16][17][18][19] . Entendemos que una adherencia tan alta está influida por diferentes factores: instalación y uso sencillos, tiempo de seguimiento (mediana 11 días) breve o la situación excepcional de estado de alarma en el momento del estudio.…”
Section: Discussionunclassified
“…La estrategia que combina telemedicina y seguimiento proactivo ha sido bien aceptada por los pacientes (solo 2 no dieron su consentimiento y hubo un alta voluntaria). Al contrario de lo que sucede en otras enfermedades, el seguimiento se completó sin grandes problemas en la mayoría de los enfermos [16][17][18][19] . Entendemos que una adherencia tan alta está influida por diferentes factores: instalación y uso sencillos, tiempo de seguimiento (mediana 11 días) breve o la situación excepcional de estado de alarma en el momento del estudio.…”
Section: Discussionunclassified
“…However, given the scope of this report, patient confidence or satisfaction was not formally assessed. Nevertheless, in this cohort of patients, there was excellent adherence, which can be a surrogate for patient acceptance [ 7 ]. Indeed, the median number of measurements per day was 3.9 in the group which did not require readmission and 5.7 in those readmitted, both higher than 97% adherence [ 7 ].…”
mentioning
confidence: 99%
“…Nevertheless, in this cohort of patients, there was excellent adherence, which can be a surrogate for patient acceptance [ 7 ]. Indeed, the median number of measurements per day was 3.9 in the group which did not require readmission and 5.7 in those readmitted, both higher than 97% adherence [ 7 ]. This may have been aided by the minimal inputs needed and the acute aspect of this illness compared to the difficulties and challenges noted in compliance with remote monitoring in chronic diseases [ 8 , 9 ].…”
mentioning
confidence: 99%
“…After confirmation of having understood the use of the TMA, the care process started. More detailed description of the telemedicine care process for participants has already been described in a previously published paper [52].…”
Section: Description Of the Tma And The Gp Treatment Regimenmentioning
confidence: 99%
“…More detailed information on the demographic data of the study participants can also be found in previously published papers [52,57].…”
Section: Study Participantsmentioning
confidence: 99%